The spread of chloramphenicol-resistant Neisseria meningitidis in Southeast Asia. (June 2020) - Batty, Elizabeth M.; Cusack, Tomas-Paul; Thaipadungpanit, Janjira; Watthanaworawit, Wanitda; Carrara, Verena; Sihalath, Somsavanh; Hopkins, Jill; Soeng, Sona; Ling, Clare; Turner, Paul; Dance, David A.B.
Highlights: Chloramphenicol resistant strains of Neisseria meningitidis are present in three countries across Southeast Asia. These strains are all closely related to each other and to resistant strains previously observed in Vietnam and France. This lineage has acquired other antimicrobial resistance genes during its spread. Abstract: Objectives: Invasive disease caused by Neisseria meningitidis is a significant health concern globally, but our knowledge of the prevailing serogroups, antimicrobial susceptibility patterns, and genetics of N. meningitidis in Southeast Asia is limited. Chloramphenicol resistance in N. meningitidis has rarely been reported, but was first described in isolates from Vietnam in 1998. We aimed to characterise eight chloramphenicol resistant meningococcal isolates collected between 2007 and 2018 from diagnostic microbiology laboratories in Cambodia, Thailand and the Lao People's Democratic Republic (Laos). Methods: Whole-genome sequencing was used to generate genome sequences from 18 meningococcal isolates including the eight chloramphenicol resistant isolates. We identified antimicrobial resistance genes present in these strains, and examined the phylogenetic relationships between strains. Results: The eight resistant strains all contain the same chloramphenicol resistance gene first described in 1998, and are closely related to each other. Strains resistant to penicillin, tetracycline, and ciprofloxacin were also observed, including a chloramphenicol-resistant strain which has acquired penicillin and ciprofloxacin resistance. Conclusions: This study suggests that chloramphenicol-resistant N. meningitidis is more widespread than previously thought, and that the previously-identified resistant lineage is now found in multiple countries in Southeast Asia.